Short-chain fatty acids mediate enteric and central nervous system homeostasis in Parkinson’s disease: Innovative therapies and their translation - Shimin Pang; Zhili Ren; Hui Ding; Piu Chan (Neural Regeneration Research)
Short-chain fatty acids, metabolites produced by the fermentation of dietary fiber by gut microbiota, have garnered significant attention due to their correlation with neurodegenerative diseases, particularly Parkinson’s disease. In this review, we summarize the changes in short-chain fatty acid levels and the abundance of short-chain fatty acid-producing bacteria in various samples from patients with Parkinson’s disease, highlighting the critical role of gut homeostasis imbalance in the pathogenesis and progression of the disease. Focusing on the nervous system, we discuss the molecular mechanisms by which short-chain fatty acids influence the homeostasis of both the enteric nervous system and the central nervous system. We identify key processes, including the activation of G protein-coupled receptors and the inhibition of histone deacetylases by short-chain fatty acids. Importantly, structural or functional disruptions in the enteric nervous system mediated by these fatty acids may lead to abnormal α-synuclein expression and gastrointestinal dysmotility, which could serve as an initiating event in Parkinson’s disease. Furthermore, we propose that short-chain fatty acids help establish communication between the enteric nervous system and the central nervous system via the vagal nerve, immune circulation, and endocrine signaling. This communication may shed light on their potential role in the transmission of α-synuclein from the gut to the brain. Finally, we elucidate novel treatment strategies for Parkinson’s disease that target short-chain fatty acids and examine the challenges associated with translating short-chain fatty acid-based therapies into clinical practice. In conclusion, this review emphasizes the pivotal role of short-chain fatty acids in regulating gut–brain axis integrity and their significance in the pathogenesis of Parkinson’s disease from the perspective of the nervous system. Moreover, it highlights the potential value of short-chain fatty acids in early intervention for Parkinson’s disease. Future research into the molecular mechanisms of short-chain fatty acids and their synergistic interactions with other gut metabolites is likely to advance the clinical translation of innovative short-chain fatty acid-based therapies for Parkinson’s disease.